2016
DOI: 10.1002/dmrr.2720
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell receptor repertoire variation may be associated with type 2 diabetes mellitus in humans

Abstract: These results indicate that T-cell autoimmunity may be an important component in progression to T2DM in Pima Indians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The complementarity determining region 3 (CDR3) of T and B cell receptor molecules plays a critical role in antigen binding [29], and abnormalities of IGH CDR3 length and hydrophobicity profile have a major impact on immune competence and self/non-self discrimination [37, 38]. A shorter CDR3 length was observed for both total and unique TRB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The complementarity determining region 3 (CDR3) of T and B cell receptor molecules plays a critical role in antigen binding [29], and abnormalities of IGH CDR3 length and hydrophobicity profile have a major impact on immune competence and self/non-self discrimination [37, 38]. A shorter CDR3 length was observed for both total and unique TRB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the peripheral T cells of patients with T2DM, the utilization of the V or J genes (especially TRBV7-8) and the amino acid lengths of the TCR CDR3 regions were significantly altered. These alterations were closely associated with an increased risk of diabetes [ 19 ]. Our study also found that the utilization of the V and/or J genes was altered in patients with AS, suggesting the relationship between TCR repertoires and atherosclerosis development.…”
Section: Discussionmentioning
confidence: 99%
“…20 T-cell receptor complementarity determining region 3 length is shorter in SAI participants with T2DM and associated with increased risk of diabetes. 21 Many autoimmune diseases show an association with certain human leukocyte antigen (HLA) haplotypes, usually involving the major histocompatibility complex class II, which encodes for genes that are important for immune response regulation. 22 A single-nucleotide polymorphism (SNP) that tags an HLA haplotype (HLA-DRB1*16:02) protective for T2DM and associated with increased insulin secretion was identified in this SAI population.…”
mentioning
confidence: 99%